Análise e implementação de um circuito de auxílio à comutação integrado aplicado a uma fonte ininterrupta de energia - Oliveira, Adriano Toniolo de (2008)
This study proposes an auxiliary commutation circuit, applied to a double-conversion uninterruptible power supply, operating with a three-level PWM full-bridge inverter. In order to construct this circuit, we use the concept of integration of auxiliary commutation circuit: the case study of ZVT. The concept of iCAC is not directly applied to three-level PWM inverters. Then, it is necessary the use of classic auxiliary commutation techniques combined with the concept of integration. In this study, it is presented a hybrid auxiliary commutation circuit. Due to the restrictions imposed by the iCAC, just one of the inverter legs can be integrated. To the other inverter leg it is used a conventional auxiliary commutation circuit. The proposed system aims at achieving a better performance if compared to the same uninterruptible power supply operating with a classic ZVT auxiliary commutation circuit. There is also the advantage that all the auxiliary switches operate with ZVS and/or ZCZ soft switching. Through the use of iCAC it is obtained a minimization of circulating reactive energy in the auxiliary commutation circuits and it contributes to increase the global performance of the uninterruptible power supply. The number of additional components is reduced in relation to the classic CAC and, consequently, the system becomes more attractive to the industry. During this study, the analysis of the system and the simulation results are presented. Finally, experimental results are presented, comparing the efficiency of the CAC iZVT proposed system versus the classic CAC ZVT, in order to validate the proposed system.